Graduated Nurses reflections from the University of La Laguna (Spain) about making a mistake in job`s context - Cristo Manuel Marrero González; Alfonso Miguel García Hernández (Universidad de Alicante, 2017)
Objective: To deepen the experience of the graduated nurses from the University of La Laguna between 2009 and 2014 regarding responsibility, insecurity and fear of error in the labor context of Tenerife (Spain). Methodology: A qualitative research is carried out with hermeneutical phenomenological approach through discourse analysis, having used as a data collection tool the semi-structured interview. Nineteen nurses participate, randomly selected and for convenience. Results: The main category is "do". It is established as the main category of the study. Of the same the following subcategories are broken down: "to make a mistake"; "Different mistakes"; "Medication errors"; "Work overload errors; "To cause death"; "Recognize mistakes and learn from them" and "act wisely". Discussion and conclusions: The meanings of the experiences are centered on making a possible mistake and its consequences. The experiences referred by the nurse with respect to responsibility are attributed fundamentally to being able to perform an adequate praxis in their work, being aware that they deal with people for it is an experience that brings much meaning to the nurse once it begins to work.